ALGORITHMIC ACCOUNTABILITY IN THE MAKING. Issue 2 (2021) - Johnson, Deborah G.
Abstract: Algorithms are now routinely used in decision-making; they are potent components in decisions that affect the lives of individuals and the activities of public and private institutions. Although use of algorithms has many benefits, a number of problems have been identified with their use in certain domains, most notably in domains where safety and fairness are important. Awareness of these problems has generated public discourse calling for algorithmic accountability. However, the current discourse focuses largely on algorithms and their opacity. I argue that this reflects a narrow and inadequate understanding of accountability. I sketch an account of accountability that takes accountability to be a social practice constituted by actors, forums, shared beliefs and norms, performativity, and sanctions, and aimed at putting constraints on the exercise of power. On this account, algorithmic accountability is not yet constituted; it is in the making. The account brings to light a set of questions that must be addressed to establish it.